Nationalism in modern Europe politics, identity and belonging since the French Revolution - Hastings, Derek (Derek Keith) (London New York Bloomsbury Academic, 2017)
"Nationalism has been, without question, one of the most potent political and cultural forces within Europe since the late-18th century. Placing particular emphasis on transnational and comparative links, Nationalism in Modern Europe provides a clear and accessible history of the development of nationalism in Europe from the French Revolution to the present. The book situates nationalist ideas and movements in Europe firmly within the context of other signifiers of identity and belonging--such as religion, race, and gender--while also providing comprehensive geographic coverage across Europe. It incorporates recent historiographical trends and debates as part of the discussion and includes 30 images, 10 maps and a range of primary source excerpts for classroom use. It is an essential volume for all students of the history of nationalism in modern Europe and a useful text for anyone seeking to know more about modern European history in general."-- Provided by publisher.
Machine generated contents note: -- List of Maps -- List of Illustrations -- 1. Introduction -- 2. The French Revolution and Napoleonic Europe, 1789-1815 -- 3. Restoration, Romanticism and Emancipatory Impulses, 1815-1850 -- 4. Industrialization, Ideological Radicalization and Imperialism, 1850-1890 -- 5. European Nationalism between Mass Politics, War and Peace, 1890-1920 -- 6. Nationalism and Belonging in an Age of Extremes, 1920-1945 -- 7. The Fate of Nationalism in a Divided Europe, 1945-1989 -- 8. Nationalism and Belonging in Europe since the Cold War -- 9. Postscript -- Bibliography -- Index.
Includes bibliographical references and index.
Keywords: Nationalism -- Europe -- History; Group identity -- Europe -- History; Europe -- Politics and government -- 1789-1900.; Europe -- Politics and government -- 20th century; Europe -- Politics and government -- 1989-.